Adult lifespan trajectories of neuromagnetic signals and interrelations with cortical thickness - Stier, Christina; Braun, Christoph; Focke, Niels K. (NeuroImage (Orlando, Fla.), 2023)
•We probed the effects of age on neuromagnetic signals during the resting-state in adults (18–88 years), interactions with sex, and correspondence with cortical thickness.•We found specific linear and non-linear associations of connectivity and power with age, indicating maturation and aging at various life stages. The findings varied regionally depending on the temporal properties of the signals and showed sex-specific effects in low-frequency bands.•Age trajectories of cortical thickness corresponded to aging patterns of delta and beta oscillations, and structure-function coupling was observed in the default mode, attention, and motor networks. Oscillatory power and phase synchronization map neuronal dynamics and are commonly studied to differentiate the healthy and diseased brain. Yet, little is known about the course and spatial variability of these features from early adulthood into old age. Leveraging magnetoencephalography (MEG) resting-state data in a cross-sectional adult sample (n = 350), we probed lifespan differences (18–88 years) in connectivity and power and interaction effects with sex. Building upon recent attempts to link brain structure and function, we tested the spatial correspondence between age effects on cortical thickness and those on functional networks. We further probed a direct structure-function relationship at the level of the study sample. We found MEG frequency-specific patterns with age and divergence between sexes in low frequencies. Connectivity and power exhibited distinct linear trajectories or turning points at midlife that might reflect different physiological processes. In the delta and beta bands, these age effects corresponded to those on cortical thickness, pointing to co-variation between the modalities across the lifespan. Structure-function coupling was frequency-dependent and observed in unimodal or multimodal regions. Altogether, we provide a comprehensive overview of the topographic functional profile of adulthood that can form a basis for neurocognitive and clinical investigations. This study further sheds new light on how the brain's structural architecture relates to fast oscillatory activity.